Plasma Proteome Responses in Salmonid Fish Following Immunization - Bakke, Fiona K.; Monte, Milena M.; Stead, David A.; Causey, Dwight R.; Douglas, Alex; Macqueen, Daniel J.; Dooley, Helen (Frontiers in Immunology, 2020)
Vaccination plays a critical role in the protection of humans and other animals from infectious diseases. However, the same vaccine often confers different protection levels among individuals due to variation in genetics and/or immunological histories. While this represents a well-recognized issue in humans, it has received little attention in fish. Here we address this knowledge gap in a proteomic study of rainbow trout (Oncorhynchus mykiss, Walbaum), using non-lethal repeated blood sampling to establish the plasma protein response of individual fish following immunization. Six trout were immunized with adjuvanted hen egg-white lysozyme (HEL) and peripheral blood sampled at ten time-points from day 0 to day 84 post-injection. We confirm that an antigen-specific antibody response to HEL was raised, showing differences in timing and magnitude among individuals. Using label-free liquid chromatography-mass spectrometry, we quantified the abundance of 278 plasma proteins across the timecourse. As part of the analysis, we show that this approach can distinguish many (but not all) duplicated plasma proteins encoded by paralogous genes retained from the salmonid-specific whole genome duplication event. Global variation in the plasma proteome was predominantly explained by individual differences among fish. However, sampling day explained a major component of variation in abundance for a statistically defined subset of 41 proteins, representing 15% of those detected. These proteins clustered into five groups showing distinct temporal responses to HEL immunization at the population level, and include classical immune (e.g. complement system members) and acute phase molecules (e.g. apolipoproteins, haptoglobins), several enzymes and other proteins supporting the immune response, in addition to evolutionarily conserved molecules that are yet uncharacterized. Overall, this study improves our understanding of the fish plasma proteome, provides valuable marker proteins for different phases of the immune response, and has implications for vaccine development and the design of immune challenge experiments.